Health risk assessment following exposure of operators to backpack-sprayed prothioconazole and its major metabolite in wheat fields in China - Li, Shuang; Mei, Chenghan; Wu, Xuemin; Li, Xuefeng; Pang, Sen (Frontiers in Environmental Science, 2023)
Prothioconazole is a triazolinthione fungicide widely used to control diseases on various crops caused by Ascomycetes, Basidiomycetes and Imperfecti fungi, etc. However, in view of the rapid transformation of parent prothioconazole to its major metabolite prothioconazole-desthio during application and the fact that the latter is of higher toxicity, prothioconazole poses a potential threat towards the health of operators in direct contact with pesticides. Currently, there are extremely scarce researches involving prothioconazole and prothioconazole-desthio exposure. Therefore, typical exposure scenario from wheat-planting provinces in China was chosen, and a motorized backpack type sprayer was used as application equipment. The actual exposure dose of prothioconazole and prothioconazole-desthio for mixers/loaders and applicators under different exposure routes were exactly determined, and tiered risk assessment was conducted in consideration of different conditions. The results of this study indicated that the exposure risk to operators after spraying with 30% prothioconazole OD (oil dispersion, OD) was unacceptable in the primary risk assessment, while the risk was acceptable with integrated risk quotients less than 1 at a better level of protection. Moreover, the upper legs and hands were regarded as the most contaminated sections during mixing/loading process, and legs were the most contaminated sections during spraying. Good protection equipment, such as wearing a hat, long-sleeve shirt, long pants, socks, and shoes, and rubber or nitrile gloves was effective measures to alleviate prothioconazole and prothioconazole-desthio exposure. This research aims to provide important references for the safe use and risk management of prothioconazole.